Analysis of the Influence of Inflation on the Real Value of Deposits on Property Purchase Accessibility - Zuhri, Mukholifatun Azizah; Ammarilia, Fidela Wanda (International Journal of Global Operations Research, 2025)
Inflation is an economic phenomenon that has a significant impact on people's purchasing power. When the inflation rate increases, the real value of money saved in the form of savings, including deposits, tends to decrease. However, when inflation exceeds the deposit interest rate, the real value of these savings will be eroded, affecting customers' ability to invest, including in purchasing property. The increase in property prices that has continued to occur in recent years has added to the challenges for people in obtaining a house or other property. Uncontrolled inflation can affect the accessibility of property purchases, because property prices often rise faster than the growth rate of deposit savings. Therefore, this study was conducted which aims to analyze the relationship between inflation and deposit interest rates offered by banks and how inflation affects the real value of money saved in the form of deposit savings over a certain period of time. This study uses a quantitative method with descriptive analysis techniques and multiple linear regression for analysis purposes. The results of the study show that high inflation reduces people's purchasing power and reduces the real value of deposit savings, while deposit interest rates that are lower than the inflation rate can reduce people's ability to buy property. This study suggests that people consider inflation in planning long-term investments, especially in the form of property.